Topology-optimized silicon-based dual-mode 4 × 4 electro-optic switch - Niu Jiaqi; Yang Shanglin; Zhou Ting; Jia Hao; Fu Xin; Zhao Zhizun; Li Zhen; Zhang Gaolu; Chen Changhua; Yang Lin (Nanophotonics)
Silicon-based optical switch is one of the key components for on-chip optical interconnect systems, and mode division multiplexing technology has been employed to boost optical switches’ channel capacity. However, the majority of the proven multimode optical switches have a switching time in the microsecond range, which is insufficient for some applications. In this paper, we design and experimentally demonstrate a high-speed dual-mode 4 × 4 optical switch based on a mode-diversity scheme, composed of four pairs of mode multiplexers and de-multiplexers, and two optimized single-mode 4 × 4 optical switches. Fast switching is enabled based on the carrier dispersion effect. At the same time, we improve the performances of the optical switch by reducing the number of optical switch units used in the 4 × 4 Spanke–Beneš architecture. Its power consumptions are reduced by ∼17%. Its insertion losses are within 8.8 dB in the wavelength range of 1525–1565 nm in the both sates of “through” and “all-cross”, while the optical signal-to-noise ratios are larger than 12.8 dB. Also, 50 Gbps data transmission experiments verify the device’s data transmission functionality.